Possibility of producing activated carbon from moringa oleifera seeds husks - Anis Farhana, Abd Razak (2014)
Cost of treatment process usually increased because of the activated carbon. Thus, there have been many researches that have been done by researchers to utilise cheaper raw materials for the production of activated carbon. Moreover, the commercially used activated carbon is coal which is limited and non – renewable which will be finish up. Consequently, a wide variety of agricultural by – products and wastes have been investigated such as coconut shell, wood, palm seed and Moringa oleifera husks. Moringa oleifera husks have the potential to produce activated carbon by carbonisation under nitrogen followed by steam pyrolysis. There are many advantages of using one – step steam pyrolysis which is no chemical inputs are required, the process requires less energy than traditional processes which involves two heating steps and local production reduce the transportation required for the product. The husks are milled, sieved and separated in fractions. Then, the samples are heated by an electric heater and are subjected to pyrolysis in the presence of steam at atmospheric pressure. The steam flow is 0.5 litre/hour and is introduced into the reactor when the temperature in the reactor is 150°C. The reactor will be heated at constant rate 25°C/min until selected temperature which are 600°C, 700°C and 800°C is reached. Then, the samples are kept at final temperature for one hour. The produced char are characterised. The surface area is calculated by nitrogen adsorption and desorption isotherms which uses dynamic flowing technique providing Brunauer, Emmett and Teller (BET) and Langmuir surface area to test whether it is micropores, mesopores or macropores. Iodine test are conducted to measure the adsorption capacity by determined the surface area.